Evaluation of a family camp intervention for children with a heart transplant and their families. (20th October 2016) - Nicholas, David B.; Dodd, Bernadette; Urschel, Simon; Young, Amber; West, Lori J.
ABSTRACT: Given the arduous course of heart transplantation and follow-up care, recipients and their families face complex challenges and stressors warranting supportive interventions. This study explored the impact of a family camp as an intervention of education and social support for pediatric transplant recipients and their families. A total of 49 individuals participated in this evaluation, including eight children and nine youth with heart transplants, five siblings, 19 parents, and 13 health care providers. Participants ranked and described the 3-day family camp experience. Analysis of pre/post intervention measures on knowledge, social support, and coping revealed statistically significant improvements in knowledge, social support, self-esteem, and psychological stability. Satisfaction surveys revealed the camp to be an important resource for education, family fun, and peer support among transplant recipients, their families, and the health care team. Implications and recommendations are offered for clinical and community practice.